2021
DOI: 10.3390/ma14185354
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dots Improved “Caterpillar”-like TiO2 for Highly Efficient Photocatalytic Hydrogen Production

Abstract: Photocatalytic water splitting for hydrogen production via heterojunction provides a convenient approach to solve the world crises of energy supply. Herein, graphene quantum dots modified TiO2 hybrids (TiO2-GQDs) with a “caterpillar”-like structure exhibit stronger light absorption in the visible region and an enhanced hydrogen production capacity of about 3.5-fold compared to the pristine TiO2 caterpillar. These results inferred that the addition of GQDs drastically promotes the interfacial electron transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…[42] It can be seen from the Figure 4 that the highresolution spectra of O are fitted to three peaks at 529.5, 531.4 and 533.1 eV, which come from the lattice oxygen in the crystal lattice, the oxygen in the hydroxyl group, and the weakly bound surface oxygen. [43] Finally, in the high-resolution spectrum of Ti element, two strong peaks can be observed at 457.7 and 463.5 eV. With the increase of the doping ratio, it can be clearly observed that the corresponding peak intensity also increases correspondingly, which verifies the result of EDS to a certain extent.…”
Section: Microstructure Characterizationsupporting
confidence: 54%
See 1 more Smart Citation
“…[42] It can be seen from the Figure 4 that the highresolution spectra of O are fitted to three peaks at 529.5, 531.4 and 533.1 eV, which come from the lattice oxygen in the crystal lattice, the oxygen in the hydroxyl group, and the weakly bound surface oxygen. [43] Finally, in the high-resolution spectrum of Ti element, two strong peaks can be observed at 457.7 and 463.5 eV. With the increase of the doping ratio, it can be clearly observed that the corresponding peak intensity also increases correspondingly, which verifies the result of EDS to a certain extent.…”
Section: Microstructure Characterizationsupporting
confidence: 54%
“…The two strong peaks can be attributed to Mn 2p 3/2 and 2p 1/2 [42] . It can be seen from the Figure 4 that the high‐resolution spectra of O are fitted to three peaks at 529.5, 531.4 and 533.1 eV, which come from the lattice oxygen in the crystal lattice, the oxygen in the hydroxyl group, and the weakly bound surface oxygen [43] . Finally, in the high‐resolution spectrum of Ti element, two strong peaks can be observed at 457.7 and 463.5 eV.…”
Section: Resultsmentioning
confidence: 92%
“…were used to calculate the positions of TiO 2 and N-GQDs in terms of valence band (VB) and conduction band (CB).where α is the absorption coe cient, h represents Planck's constant, ν refers to frequency of the light, A is the proportional constant, E g is the energy of band gap, E VB stands for the edge potential of VB, χ is the electronegativity of the semiconductor (about 5.81 eV for TiO 2(Hao et al 2016)), E e represents the energy of free electrons on the hydrogen scale (about 4.5 eV vs. NHE) and E CB is the edge potential of CB.As shown in Fig.10(b), the calculated E g values of neat TiO 2 , N-GQDs and TGs 4 composites were 3.20, 2.44 and 3.01 eV, respectively, and the E VB value of TiO 2 was calculated to be 2.91eV. According to previous study, the E VB of N-GQDs was about 1.41 eV(Ma et al 2021). Consequently, the E CB values of TiO 2 and N-GQDs were estimated to be -1.03 and − 0.29 eV, respectively.…”
mentioning
confidence: 57%
“…It can be used to degrade hazardous organic materials [3][4][5][6], prepare self-cleaning and solar-cleanable membrane surfaces used in membrane photoreactors [7][8][9], or produce green energy sources from organic pollutants [10][11][12][13]. Moreover, the utilization of photocatalytic nanomaterials is not limited to water purification; they are essential in the development of air-cleaning processes [1,14,15], self-cleaning surfaces [16][17][18], photocatalytic water splitting [19,20], and artificial photosynthesis [21,22]. TiO 2 is the most widely investigated photocatalyst because of its numerous favorable properties.…”
Section: Introductionmentioning
confidence: 99%